Proposed Marketing Strategy for Carwash Business (Case Study: C’Monk Carwash) (The Indonesian Journal of Business Administration, 2020)
Bandung is the fourth most populous city in Indonesia, and is the most populous city in Indonesia. The reason is because the Bandung city is an attractive tourist destination and has various types of tourist destinations. This was accompanied by an increase in the number of vehicles in Indonesia, especially in the city of Bandung and its surroundings, which further strengthened the survey that the Bandung city was the most populous city in Indonesia. This fact provides an opportunity to do car wash service businessOne of the companies engaged in this vehicle washing service is C’Monk, which was established in 2017 and is located on Jl. Sadakeling No. 18 A Bandung. Right now, the problem faced by C'Monk is that there is no marketing strategy to increase sales. To solve this problem, it is necessary to create a new marketing strategy based on consumer opinion to further improve the services provided by C’MonkThe results show that the most ideal marketing strategy for C’Monk is to increase the awareness of potential customers through social media, build collaboration with other businesses in the automotive field, and at the same time improve the quality of services provided by C’Monk Keywords: Service Marketing Mix, SWOT Analysis, TOWS Matrix Analysis, Business Model Canvas, Carwash Business